Cidade de Deus, lugar pobre e violento. Articulando representações sociais - Franqueira, Bruno Dias (2011)
The expressive reproduction of poverty and violence in the mass media, as seen in the contemporary Brazilian cinema, involve studies in several areas of the human science and social science. This research aims to contribute with these studies, aiming at the understanding of social representations of poor place, violent place and the film City of God. The theoretical and methodological contribution used in this research was the Theory of the Central Nucleus of Social Representations. One hundred people participated in this research, divided by two groups; Group 01 was a group formed by fifty residents of middle class and high class neighborhoods and Group 02 was formed by fifty residents of suburb neighborhoods; both groups consisted of residents of Vitória County and Vila Velha County of the state of Espírito Santo. The data was collected by a questionnaire consisted of open and closed questions of free evocations. The determination of the peripheral elements and the central cores of the representations were made using the EVOC software. The results showed that the social representations of poor place are related to the structural deficiencies of the suburbs, also related to violence, and individual and collective needs; the social representations of poor place are related to drug trafficking, different types of violence and deaths resulting from the use of firearms; and the representations of the movie City of God provide elements of the representations of poor place and violent place. The similarities among elements of the representation of objects allow reflections on the role of the media in processes of communication as trainers and breeders of social representations.